CD40L Deficiency Protects Against Aneurysm Formation. Issue 5 (May 2018) - Kusters, Pascal J.H.; Seijkens, Tom T.P.; Beckers, Linda; Lievens, Dirk; Winkels, Holger; de Waard, Vivian; Duijvestijn, Adriaan; Lindquist Liljeqvist, Moritz; Roy, Joy; Daugherty, Alan; Newby, Andrew; Gerdes, Norbert; et al.
Abstract : Objective—: The mechanisms underlying formation of arterial aneurysms remain incompletely understood. Because inflammation is a common feature during the progressive degeneration of the aortic wall, we studied the role of the costimulatory molecule CD40L, a major driver of inflammation, in aneurysm formation. Approach and Results—: Transcriptomics data obtained from human abdominal aortic aneurysms and normal aortas revealed increased abundance of both CD40L and CD40 in media of thrombus-free and thrombus-covered human abdominal aortic aneurysms samples. To further unravel the role of CD40L in aneurysm formation, apolipoprotein E–deficient ( Apoe −/− ) and Cd40l −/− Apoe −/− mice were infused with angiotensin II for 7 and 28 days. Only a minority of Cd40l −/− Apoe −/− mice (33% and 17%) developed (dissecting) aneurysms compared with 75% and 67% of Apoe −/− littermates after 7 and 28 days of infusion, respectively. Total vessel area of the aorta at the suprarenal level was 52% smaller in angiotensin II–infused Cd40l −/− Apoe −/− mice compared with that in angiotensin II–infused Apoe −/− mice. Chimeric Apoe −/− mice repopulated with Cd40l −/− Apoe −/− bone marrow afforded a similar protection against dissecting aneurysm formation. Moreover, lack of CD40L protected mice from fatal aneurysm rupture. T helper cell and macrophage accumulation in aneurysmal tissue was reduced in Cd40l −/− Apoe −/− mice with a concomitant decrease in expression of proinflammatory chemo- and cytokines. In addition, aneurysms of Cd40l −/− Apoe −/− mice displayed reduced abundance of matrix metalloproteinase-13 and an increase in tissue inhibitor of metalloproteinase-3 while activity of matrix metalloproteinase-2 and matrix metalloproteinase-9 was diminished. Conclusions—: Deficiency of (hematopoietic) CD40L protects against dissecting aneurysm formation and reduces the incidence of fatal rupture. This is associated with a decreased accumulation and activation of inflammatory cells and a dampened protease activity in the arterial wall. Abstract : Supplemental Digital Content is available in the text.